Pengembangan LKPD Pada Pembelajaran Tematik Menggunakan Model Role Playing Di Kelas V Sekolah Dasar - Elwisa Hekmatulaini; Puspa Djuwita; Sri Dadi (Universitas Bengkulu, 2020)
This study aims to produce LKPD on Thematic Learning using a role playing model in class V SD Negeri Bengkulu City. This study is a Research and Development (R&D) research by modifying the 4-D model by Thiagarajan and Sammel. However, this research was only carried out until the third stage, namely Develop (Development). Validation is carried out by RPP experts and LKPD experts. The developed LKPD was given a score and responses by 8 students. Data analysis techniques used descriptive analysis of expert validation assessments and student responses as well as qualitative descriptive analysis of comments from expert validation and student responses. This research resulted in the development of LKPD in thematic learning using a role playing model with assessments from LKPD experts in stage 1 of 78, 15 in good categories, in stage 2 of 89, 20 with very good categories and 90 student responses with very good categories. So, the research that has been carried out can be concluded that the LKPD uses the role playing model in thematic learning in grade V SD can be categorized as a very good LKPD and can be used in learning at school.Keywords: LKPD, Development, Role Playing, Thematic.